THE INFLUENCE OF SERVICE MARKETING MIX ON CUSTOMERS’ DECISIONS TO VISIT ECO GREEN PARK - Tia Dewanti Sylvina Sari Saksono; Ainur Rofiq (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The aim of this research is to examine the influence of service marketing mix on customers’ decisions to visit Eco Green Park. It focuses on investigation to reveal the effect of product, price, place, promotion, people, process and physical evidence on customer decision. The samples of this research is visitors of Eco Green Park. The sampling technique used was purposive sampling and the research instrument was tested using validity and reliability test. The hypotesis was tested using t test from multiple regression analysis. The results show that product, place and physical evindence have significant effects on Customer Decision. However, price, promotion, people and process have not significant effects on Customer Decision..Keywords: Product, Place, Price, Promotion, People, Process, Physical Evidence, Customer Decision, Eco Green Park.